Language teacher perspectives on stress and coping. (18th June 2021) - Gregersen, Tammy; Mercer, Sarah; MacIntyre, Peter D.
Abstract: Every person's response to adversity is unique. Whereas some come out stronger as a result of responding to a challenge, others find their fundamental assumptions about themselves and their lives severely challenged. In education, while some teachers might burn out and leave the profession precipitously, many survive the challenges and transform teaching into their lifelong passion. What factors help explain why some language teachers remain resilient and experience growth after trauma, while others suffer a sense of loss, depleted psychological resources, and ultimately succumb to the pressures of the job, leaving the profession or burning out? The purpose of this study was to seek answers to this question in the context of teaching during the Covid‐19 pandemic, which represents a specific unprecedented type of adversity. To do this, 765 foreign language teachers worldwide answered an online questionnaire that asked three open‐ended questions about the stressors and uplifts they were experiencing during the first few months of the pandemic. Respondents were invited to offer their advice to other language teachers who were facing the challenge of teaching during this time. The Challenge: Language teachers differ in their response to challenges that arise in their personal and professional lives, and the current global pandemic is no different. What do the voices of practicing language teachers tell us about their stressors and uplifts as they navigate adversity? How do their narratives mark different pathways through adversity?